2004
DOI: 10.1111/j.1525-1497.2004.30395.x
|View full text |Cite
|
Sign up to set email alerts
|

Does patient-centered care improve provision of preventive services?

Abstract: Improved communication between patients and providers, and continuity of care are associated with increased provision of preventive services, while other aspects of PCC are not strongly related to delivery of preventive services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 46 publications
4
49
1
Order By: Relevance
“…8,21,22 Several other studies have found improvement in preventive services and utilization with increased continuity of care, but only Belardi et al have found an association between access improvements and continuity of care (and that was in a residency clinic). [23][24][25] Results show the importance of including a separate focus on continuity of care when working to improve access, which is what this medical group did in its access transformation. Some groups, however, appear to have created access changes in such a way that continuity would be likely to deteriorate by not allowing patients to preschedule follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…8,21,22 Several other studies have found improvement in preventive services and utilization with increased continuity of care, but only Belardi et al have found an association between access improvements and continuity of care (and that was in a residency clinic). [23][24][25] Results show the importance of including a separate focus on continuity of care when working to improve access, which is what this medical group did in its access transformation. Some groups, however, appear to have created access changes in such a way that continuity would be likely to deteriorate by not allowing patients to preschedule follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an excellent patient-physician rapport as well as continuity of care was correlated with improved preventive care delivery [60]. Two aspects of patient-centered care, effective communication and continuity of care, are especially important [45].…”
Section: Patient Centered Care -Clinical Conveniencementioning
confidence: 99%
“…[34][35][36][37] A clinician engaging in patient-centered, shared decision making may be most likely to tailor specific behavioral recommendations for patients to consider, adjust the amount of information conveyed, and arrange referrals to appropriate external resources. Provider perceptions of low personal efficacy to influence weight loss, a lack of treatment efficacy and/or futility, and patient resistance to interventions all play potential roles in reducing provider involvement in obesity treatment.…”
Section: Discussionmentioning
confidence: 99%